The effect of geometry on the flexural properties of cellular core structures. (March 2019) - Araújo, H; Leite, M; Ribeiro, AR; Deus, AM; Reis, L; Vaz, M Fátima
Composite sandwich materials are very common in structural uses for a wide range of applications in the aerospace and automotive industry that require low weight, high bending strength, and high energy absorption. In general, the core of the sandwich structures has a two-dimensional cellular structure, with a regular honeycomb geometry. While with standard manufacturing processes the geometric structures are limited, the emergence of additive manufacturing provides alternatives to conventional designs. The aim of this work is to analyze and evaluate the effect of the core geometry on the flexural properties of the structure. For that purpose, three different cellular configurations were considered, namely regular honeycombs, lotus, and hexagonal honeycombs with Plateau borders. Four relative densities, with average values of 0.1, 0.25, 0.44, and 0.62, for each configuration, were studied. The flexural properties of cellular structures were evaluated with three-point bending tests, both numerically and experimentally. A modeling approach of the tests in the three configurations was performed, for two materials, polylactic acid and pure aluminum, by means of finite element simulations. Fused deposition modeling was used to obtain polylactic acid samples for the aforementioned configurations, which were experimentally tested to evaluate the mechanical response and the failure behavior of the cores. Results differ with the geometry arrangement and showed a strong dependency with the relative density of the structures in the flexural response in what concerns strength, stiffness, and energy absorbed. The arrangements studied present properties, which make them competitive with the traditional core structures for the same density. A promising agreement between experimental and simulation results was obtained.